Effects of Covert and Overt Modeling on the Communication of Empathy - Uhlemann, Max R.; Koehn, Corinne V. (Canadian Journal of Counselling and Psychotherapy, 2011)
This study examined the efficacy of imagery used in covert modeling and compared it with the efficacy of overt modeling alone on the acquisition of empathy responding. Sixty-four participants were assigned randomly to one of the following four experimental conditions: covert modeling, long overt modeling, short overt modeling and no-treatment control. Posttest written and oral measures of empathie responding were obtained. Data analysis indicated that participants in the three treatment conditions had a significantly higher quality of empathie responses on both measures than did the control participants. The findings indicated that imagery, inherently present in the covert modeling procedure when teaching verbal skill, did not enhance skill performance over that of overt modeling alone. Implications for counsellor training and future research are presented.